Effectiveness of Complementary Therapy on Blood Pressure in Hypertension Patients: A Literature Review - Vivi Syofia Sapardi; Ria Desnita; Defrima Oka Surya (GLOBAL HEALTH SCIENCE GROUP, 2025)
Management of hypertension can be done pharmacologically and non-pharmacologically. Pharmacologically by consuming medication to control blood pressure. Whereas non-pharmacologically, it can be done through the provision of complementary therapy. Complementary therapy is not only for lowering blood pressure but also for addressing various physical and psychological complaints related to hypertension. Some complementary therapies found to help lower blood pressure include progressive muscle relaxation, slow stroke back massage, guided imagery, hypertension exercise, aromatherapy, music therapy, and murotal. The purpose of this literature review is to determine the effectiveness of several types of complementary therapies on blood pressure in hypertensive patients. The literature review search uses the PubMed and Google Scholar databases. The literature search started with articles published from 2019 to 2024. The inclusion criteria used in the selection of this literature review are original research, full text, the period from 2019 to 2024, experimental studies with complementary therapy interventions, and research results showing the effectiveness of the therapy. Whereas the exclusion criteria are studies that do not focus on complementary therapy for hypertension patients. Based on the literature review, 6 articles were found that examined complementary therapy interventions showing significant results in lowering blood pressure in hypertensive patients. The conclusion of this literature review is that complementary therapies such as progressive muscle relaxation, slow stroke back massage, guided imagery, hypertension exercises, aromatherapy, music therapy, and murotal are effective in lowering blood pressure in hypertensive patients.